Toughening epoxy resins with soluble hyperbranched poly (aryl ether ketone): enhanced mechanical properties and thermal stability - Xiyan Li; Feng Bao; Shuang’er Li; Tang Zhu; Jiali Yu; Qing Zhang; Huichao Liu; Caizhen Zhu; Jian Xu (Advanced Manufacturing: Polymer & Composites Science)
The limited toughness of epoxy resins (EP) significantly hinders their application. While hyperbranched polymers are commonly employed as toughening agents, their poor solubility often leads to drawbacks, including a marked reduction in glass transition temperature (Tg). In this study, a novel hyperbranched poly (aryl ether ketone) resin (pm-HBPAEK-OH) with enhanced solubility was synthesized and evaluated as a toughening agent, for EP. The results indicated that when the content of pm-HBPAEK-OH is 6%, the tensile strength, flexural strength, impact strength, and elongation at break reached 75.1 MPa, 113.8 MPa, 43.5 kJ/m2, and 11.3%, respectively, representing enhancements of 10.0%, 13.1%, 112.9%, and 195.0% compared to the pure EP. Additionally, the modified EP exhibited superior thermal stability achieving a Tg of 91.6 °C, which is approximately 15.4 °C higher than that of pure EP, without a significant loss in thermal decomposition temperature.